A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 1 PEKANBARU IN COMPREHENDING SHORT FUNCTIONAL TEXTS - Ningrum, Nurdwi Ayu Setia; ', Eliwarti; Ras, Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This descriptive research was aimed at finding out the ability of the second year students of SMPN 1 Pekanbaru in comprehending short functional texts. This research focuses on students’ comprehending three kinds of short functional text in terms of advertisement, invitation card and short message text. The data were collected by usingreading comprehensiontest with multiple choice types. The test contained 36 items. The population were the second year students of SMPN 1 Pekanbaru in academic year 2016/2017.The sample size was 40 students out of the population, chosen by using cluster random sampling technique.Based on the data analysis, each type of short functional texts is in the good level with the mean score of 60.98, advertisement, 62.68 is in the good level, invitation card, 58.31is in mediocre level and short message text, 63.10 is in good level.As a conclusion, the highest score obtained by the students is in comprehending short message text with the mean score of 63.10 which is categorized into good level. The lowest score among three types of short functional text is in comprehending invitation card, with the mean score of 58.31 which is categorized into mediocre level. The implication of the findings is that the students need to learn more seriously about short functional text, particularly about invitation card.Keywords: Reading Ability, Short Functional Text.